THE EFFECT OF MURABAHAH, MUSYARAKAH, AND IJARAH FINANCING ON PROFITABILITY WITH NON PERFORMING FINANCING AS A MODERATION VARIABLE IN ISLAMIC COMMERCIAL BANKS FOR THE 2016-2020 PERIOD - Anisya Putri Nurmala Sari; Maharani (Transpublika Publisher, 2022)
This study aims to examine the effect of Murabahah, Musyarakah and Ijarah financing on Profitability with Non-Performing Financing (NPF) as a moderating variable at Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK) in the 2016-2020 period. This type of research is quantitative. Data is obtained by accessing financial reports and annual reports through the website of each Islamic Commercial Bank. The sampling method used is purposive sampling method using criteria so that a sample of 8 (eight) companies can be obtained for 5 (five) years of observation. This research was conducted using an analysis that includes descriptive statistical tests, capital estimation approach tests, panel data regression models, classical assumption tests, coefficients of determination (r^2) tests, partial tests, simultaneous tests and moderated analysis regression (MRA) tests through software Eviews 10. The results of this study indicate that murabahah financing has a positive and significant effect on the profitability of Islamic commercial banks as measured by ROA, musyarakah financing has a negative and significant effect on the profitability of Islamic commercial banks as measured by ROA and ijarah financing has no negative and significant effect on profitability. Islamic Commercial Banks as measured by ROA. Non-performing financing moderates murabaha financing on the profitability of Islamic commercial banks in Indonesia, Non-performing financing does not moderate musyarakah financing on the profitability of Islamic commercial banks in Indonesia and Non-performing Financing does not moderate Ijarah financing on the profitability of Islamic commercial banks in Indonesia.